The effect of servant leadership on the organizational citizenship behavior of instructors in public universities in Amhara region - Shimelis Mesfin (Cogent Business & Management, 2024)
The purpose of this study was to examine the effect of servant leadership on the organizational citizenship behavior (OCB) of instructors in public universities in Amhara region. An explanatory sequential mixed research design was employed. The size of the population was 2170. Of these, 338 instructors were taken into the sample using Yamane's (1973) formula. Questionnaires and interviews were used to collect the data. Both quantitative and qualitative analysis techniques were used to analyze the data. The results obtained through the questionnaire and interview revealed that servant leadership and OCB were practiced moderately in the universities. There was a positive and statistically significant relationship between servant leadership and OCB with a standardized correlation coefficient (r = .578) by the critical ratio test greater than ± 1.96 at p < .05.Thus, 33.4 % of the variance in OCB was predicted by servant leadership with standardized regression coefficient (β =.578) at p < .05.The result of one way ANOVA indicated that significant differences were observed among instructors in their perception of servant leadership and OCB. Based on the finding of this study, it is concluded that servant leadership had a significant effect on the OCB of instructors. Therefore, it is suggested to improve the implementation of servant leadership and OCB.
Keywords: 650; instructors; organizational citizenship behavior; public universities; servant leadership